DEVELOPING LIFESPAN IMPROVEMENT DISTRICTS (LIDS): LESSONS LEARNED FROM USC'S AGE-FRIENDLY LOS ANGELES PRACTICUM. (11th November 2018) - Cicero, C; Nguyen, A L; Swift, J; Ruddell, D; Banerjee, T; Ailshire, J
Abstract: To address age-friendly domains and consider the lifespan challenges Los Angeles' diverse and expansive topography and built environment pose, the authors created an interdisciplinary practicum at the University of Southern California for students from four academic units. Masters students and faculty set out to depict age-friendliness in digital terms, with story maps and interactive apps, seeking stakeholder input in a GeoDesign Charrette, neighborhood audits, and community evaluations. Charrette outcomes determined that in a megacity such as Los Angeles, the study of age-friendliness requires contained, geographical areas to evaluate. We coined these areas Lifespan Improvement Districts. Students subsequently evaluated the age-friendless of six distinct geographies and created websites and apps for public use and education, policy advocacy, and further research. This presentation will describe the process and outcomes of the interdisciplinary course, challenges, lessons learned, and next steps including partnering with local stakeholders in developing policy alternatives.